Assessment of Urban Resiliency Concerning Disaster Risk: A Review on Multi- Dimensional Approaches - Roy, Tusar Kanti; Siddika, Sharmin; Sresto, Mizbah Ahmed (Journal of Engineering Science, 2022)
There have been a number of new research published with different methodologies and frameworks in recent years, aimed at improving city resilience to a variety of man-made and natural calamities. As climate change progresses, resilience will become a more important topic in scientific and policy circles that influence future urban development. This review article first provides the definition of resilience. Then it represents some of the adopted methodologies in an extensive way. Approaches including Baseline Resilience Indicators for Communities (BRIC), Climate Disaster Resilience Index (CDRI), Disaster resilience index based on Analytic Hierarchy Process (AHP), Composite indicator based approach, Hyogo Framework and so on. This section discusses about urban resiliency assessments to mitigate vulnerability, offer a set of principles and indicators for creating an urban resilience assessment tool. Findings of this study not only address a variety of qualitative and quantitative aspects of urban resilience but also describes about different indicators such as environmental resources, socio-economic and built environment, infrastructure, governance and institutional indicators. Journal of Engineering Science 12(3), 2021, 111-125